Respostas

2014-06-03T22:17:06-03:00
(x + 2).(x – 2).(x + 1).(x – 1) + 5x2 = 20

(x
² - 2x + 2x - 4) × (x² - x + x - 1) + 10 = 20

x^4- x² - 4x² + 4 + 10 = 20 ⇒ x^4 - 5x² + 14 = 20

x^4 - 5x² + 14 - 20 ⇒ x^4 - 5x² - 6 = 0

o x^4 pode ser escrito assim: (x²)². ou seja: x² = y, então onde for x², eu vou vou colocar o y

(x²)² - 5x² - 6 = 0 ⇒ y² - 5y - 6 = 0

Agora resolve normal

Δ = b² - 4ac ⇒ (-5)² - 4 × 1 × (-6) ⇒ 25 + 24 ⇒ Δ = 49

y = - b ± √Δ / 2a ⇒ -(-5) ± √49 / 2 × 1

y = 5 ± 7 / 2  y' = 6         y'' = -1
1 5 1